Optimal monetary policy according to HANK - Sushant Acharya; Edouard Challe; Keshav Dogra (Bank of Canada, 2021)
We study optimal monetary policy in an analytically tractable Heterogeneous Agent New Keynesian model with rich cross-sectional heterogeneity. Optimal policy differs from that in a representative agent model because monetary policy can affect consumption inequality by reducing both idiosyncratic consumption risk and the inequality that arises from households' unequal exposures to aggregate shocks. Simple target criteria summarize the planner's tradeoff between consumption inequality, productive efficiency and price stability. Mitigating consumption inequality requires putting some weight on stabilizing the level of output and correspondingly reducing the weights on the output gap and the price level relative to an economy without inequality.
Keywords: E21; E30; E52; E62; E63; 330; Economic models; Monetary policy